PENGARUH LEVERAGE, SALES GROWTH, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Wina Anindya; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the effect of leverage, sales growth, company size and profitability on earnings management. The population in this research is all the companies in the manufacturing sector on the Indonesia Stock Exchange during period 2016 to 2018. This research use the sampling data of 41 firms. The sampling is based on the method of purposive sampling. The research is a quantitative research using classic assumption test and multiple linear regressions analysis.The result of this research shows that proportion of leverage, size, and profitability have no significant effect on earning management. While sales growth has a significant positive effect on earning management.